Telestration with augmented reality improves surgical performance through gaze guidance - Felińska, Eleni Amelia; Fuchs, Thomas Ewald; Kogkas, Alexandros; Chen, Zi-Wei; Otto, Benjamin; Kowalewski, Karl-Friedrich; Petersen, Jens; Müller, Beat P.; Mylonas, George; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2023)
In minimally invasive surgery (MIS), trainees need to learn how to interpret the operative field displayed on the laparoscopic screen. Experts currently guide trainees mainly verbally during laparoscopic procedures. A newly developed telestration system with augmented reality (iSurgeon) allows the instructor to display hand gestures in real-time on the laparoscopic screen in augmented reality to provide visual expert guidance (telestration). This study analysed the effect of telestration guided instructions on gaze behaviour during MIS training.
Published online: 6 January 2023
Gesehen am 15.05.2023